Voltage Pulse Induced Resistance Change Response of ReRAM with HfO2 Layer. (20th July 2018) - Azuma, Atsushi; Nakajima, Ryo; Yoshida, Hayato; Shimizu, Tomohiro; Ito, Takeshi; Shingubara, Shoso
Abstract : Neuromorphic devices have been actively studied recently. Resistive Random Access Memory (ReRAM) attract attention not only for nonvolatile memory but neuromorphic synaptic device. In this study, we investigated ReRAM devices with a Hf-oxide dielectric layer as an artificial synapse. We used Ti top electrode and Pt or Au bottom electrode for the ReRAM device and applied a train of constant voltage pulses to study resistance change response of the device. We applied voltage pulses in the RESET process as well as in the SET process to observe resistance change response. In the RESET process of the Ti/HfO2 /Pt device, it showed gradual resistance change response with increase of a number of voltage pulses. However, the resistance exhibited binary change in the case of SET process. On the other hand, in the case of Ti/HfO2 /Au device, it showed gradual resistance change with increase of a number of voltage pulses for both SET and RESET processes. From XPS depth analysis, it turned out that Au atoms diffused into the Hf-oxide layer in the Ti/HfO2 /Au device, although Pt atoms did not diffuse into the Hf-oxide layer in the Ti/HfO2 /Pt device. In the case of Ti/HfO2 /Au device, both oxygen vacancies and Au atoms contribute to hopping conduction, which seems to be an origin of the gradual change of resistance due to voltage pulses in both SET and RESET processes. From these experiments, we may conclude that the Ti/HfO2 /Au device is more suitable for artificial synapse device than Ti/HfO2 /Pt device.